Effect of 2% Chlorhexidine as an Irrigant on Postoperative Symptoms Following Foraminal Instrumentation: A Randomized Clinical Trial - Fernanda Garcias Hespanhol; Ludmila Silva Guimarães; Erlange Andrade Borges da Silva; Lívia Azeredo Alves Antunes; Leonardo Santos Antunes (Association of Support to Oral Health Research (APESB), 2024)
Objective: To compare postoperative pain, tenderness, edema, and medication use after foraminal enlargement in a single visit, using 2.5% sodium hypochlorite (NaOCl) and 2% chlorhexidine gel (CHX). Material and Methods: Seventy patients with single-rooted teeth with apical periodontitis were randomized into two groups according to the irrigation protocol: control (NaOCl - 35 patients) and case (CHX - 35 patients). Pain intensity was assessed using the visual analog scale (recorded every day for seven days, on the 14th and 30th days after treatment). Edema was assessed by two independent evaluators on the 2nd, 3rd, and 7th days after treatment using photographs. Data were analyzed using Chi-square, Fisher's Exact, and Mann-Whitney U tests in SPSS. Results: There was a statistically significant difference in postoperative pain and tenderness between the groups on the 2nd day (p<0.05). There was no difference between the groups for edema (p=1.00) and use of medication (p=0.77). Conclusion: Chlorhexidine resulted in more significant postoperative pain and tenderness after foraminal enlargement.